THE INFLUENCE OF COMPETENCE AND ORGANIZATIONAL COMMITMENT ON TEACHER PERFORMANCE MODERATION BY ACADEMIC SUPERVISION (Case Studyon Teachers in Kesatrian Senior High Schoolunder TheKesatrianEducation Foundation 67) - Undang Lukman Hakim, 1352020074; Basiya, Robertus (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimsto analyze Influence of Competence and Organizational Commitment on theteachers Performance of senior high school Kesatrian under the auspices of the Kesatrian 67 Education Foundation of Semarang with Academic Supervision as moderaration variable. TheÂ  population of this study are 102 respondents, this study is explanatory research. By all the criteria ofÂ  senior high school Kesatrian teachers under the auspices of the Kesatrian 67 Education Foundation of Semarang. Measurements used a Likert scaleÂ  of five alternative answers. Test instruments used are validity and reliability, while the normality test used Kolmogorov-Smirnov statistics. Heteroskedastisitas test used Glejser method, test model used is F test (Goodness of fit) and the coefficients of determination (Adjusted R square), while hypotesis test used regression analysis with t-test at the 0,05 significance level. The results of this study are: (1) the Competence has positive and significant effect on teacher performance, (2) the Organizational Commitment doesnât haveeffect on the Â teacher performance, (3) Academic Supervision has positive and significant effect on teacher performance, (4) Academic Supervision has moderateinfluence Competence on the Teacher Performance (5) Academic supervision doesnât moderate influence Organizational Commitment on the teacher Performance. Keyword: Competence, Organizational Commitment, Academic Supervision, Teacher Performance. Â